В тридевятом царстве: русские народные сказки / [художники Д. Вдовенко, Е. Рубцова] - Вдовенко Д. (10 сказок малышам, 2016)
Экземпляры: 2 (20160728) / Инвентарный номер: 60940 / Цена: 150.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 11 / ББК: 84(2Рос=Рус)6